Challenges of stroke prevention in patients with atrial fibrillation in clinical practice. - Hobbs, F; Leach, I (2011)
Strokes and transient ischaemic attacks in patients with atrial fibrillation (AF) can be largely prevented. Risk stratification and appropriate prophylactic regimens help to alleviate the burden of AF-related thromboembolism. Guidelines recommend routine anticoagulation with oral vitamin K antagonists (VKAs) for patients at moderate-to-high risk of stroke, and acetylsalicylic acid (ASA) for those at low risk of stroke. ASA is less effective at reducing the risk of stroke than VKAs; however, ASA does not require monitoring or dose adjustment. Trials of anticoagulants show consistent benefits of oral VKAs for primary and secondary stroke prevention in patients with AF. Nevertheless, VKAs do require frequent coagulation monitoring and dose adjustment because of their variable dose-response profile, narrow therapeutic window, increased risk for bleeding complications and numerous food and drug interactions. This review aims to provide an overview of the clinical challenges of anticoagulant therapy for the prevention of stroke in patients with AF.